Risk of hospitalised bleeding in comparisons of oral anticoagulant options for the primary treatment of venous thromboembolism. (28th March 2019) - Lutsey, Pamela L.; Zakai, Neil A.; MacLehose, Richard F.; Norby, Faye L.; Walker, Rob F.; Roetker, Nicholas S.; Adam, Terrence J.; Alonso, Alvaro
Summary: Understanding of the comparative bleeding risks of oral anticoagulant (OAC) therapies for the primary treatment of venous thromboembolism (VTE) is limited. Therefore, among anticoagulant‐naïve VTE patients, we conducted comparisons of apixaban, rivaroxaban and warfarin on the rate of hospitalised bleeding within 180 days of OAC initation. MarketScan databases for the time‐period from 2011 to 2016 were used and, for each OAC comparison, new users were matched with up to five initiators of a different OAC. The final analysis included 83 985 VTE patients, who experienced 1944 hospitalised bleeding events. In multivariable‐adjusted Cox regression models, rate of hospitalised bleeding was lower among new users of apixaban when compared to new users of rivaroxaban [hazard ratio (95% confidence interval) 0·58 (0·41–0·80)] or warfarin [0·68 (0·50–0·92)]. Overall, the hospitalised bleeding rate was similar when comparing new users of rivaroxaban to new users of warfarin [0·98 (0·68–1·11)], though there was some suggestion that rivaroxaban was associated with lower bleeding risk among younger individuals. Findings from this large real‐world population concur with results from the randomised trial which found lower bleeding risk with apixaban versus warfarin and, for the first time, reveal a lower risk of bleeding in a comparison of apixaban versus rivaroxaban.